The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1021/acs.cgd.6b00274
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Supramolecular Isomerism of Lutetium-Aminoterephthalate Metal–Organic Frameworks: Synthesis, Crystallography, and Physical Properties

Abstract: Three supramolecular isomers of lutetium metal-organic framework, {Lu 2 (H 2 O) 4 (ATA) 3 ·4H 2 O} n (Lu-ATA@RT), {Lu 2 (H 2 O) 2 (C 3 H 7 NO) 2 (ATA) 3 } n (Lu-ATA@100) and{Lu 2 (C 3 H 7 NO)(ATA) 3 } n (Lu-ATA@150), have been obtained from the reaction of Lu(NO 3 ) 3 ·6H 2 O with 2-aminoterephthalic acid (ATA) at different temperatures. The resulting structures of Lu-ATA MOFs depend on the temperature applied during the synthesis, revealing a temperature-susceptible supramolecular isomerism. Single-crystal X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 65 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Zaworotko has extended the concept of isomerism in monomeric metal complexes to oligomeric and polymeric coordination compounds and called it supramolecular isomerism. Similar to the importance of polymorphism in the pharmaceutical area, , supramolecular isomerism is academically challenging and may serve the fundamental understanding for the development of metal-organic framework-based functional materials. As controlling factors leading to supramolecular isomerism, temperature, solvent, template, guest, , pH, catenation, mole ratio, and concentration have been known in the self-assembly of metallosupramolecules. However, the role of the solvent in this area has been less understood than other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Zaworotko has extended the concept of isomerism in monomeric metal complexes to oligomeric and polymeric coordination compounds and called it supramolecular isomerism. Similar to the importance of polymorphism in the pharmaceutical area, , supramolecular isomerism is academically challenging and may serve the fundamental understanding for the development of metal-organic framework-based functional materials. As controlling factors leading to supramolecular isomerism, temperature, solvent, template, guest, , pH, catenation, mole ratio, and concentration have been known in the self-assembly of metallosupramolecules. However, the role of the solvent in this area has been less understood than other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular isomers which have an identical chemical composition but different network structures or morphologies have received increasing attention in the molecular and crystal engineering areas. A number of studies on the supramolecular isomerism have been reported so far, and the factors such as temperature, solvent, template, pH, , catenation, molar ratio, , and concentration have been found to affect the formations of particular supramolecular isomers. However, it is still important to find and understand the factors that induce the formation of supramolecular isomers.…”
Section: Introductionmentioning
confidence: 99%
“…CPs are typically built up through solvothermal or hydrothermal reactions in a closed autoclave, but it is still challenging to rationally design and construct CPs with desired topological structures due to complicated extrinsic factors, such as reaction temperature (Dikhtiarenko et al, 2016), template agents/additives (Hu et al, 2013), pH (Yang et al, 2012) and solvents (Xu et al, 2012). Since metal ions and organic ligands are the main inorganic and organic building units of CPs, it is generally believed that their selection and combination play a crucial role in determining the final network (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%